Influence Of Auditor Switching, Audit Fee, Tenure Audit and Company Size To Audit Quality - Lia Dama Yanti; Michael Darmawan Wijaya Darmawan Wijaya (Komunitas Dosen Indonesia, 2020)
Audit quality is a function of the auditor's independence and competence of the company's management in examining and providing opinions on the company's financial statements so that the auditor can report violations in a financial statement. This study aims to determine the effect of auditor switching, audit fees, audit tenure and company size on audit quality in food and beverage companies listed on the Indonesia Stock Exchange for the period 2015-2018 This research is an Ex-Post Facto research with data collection methods using secondary data. The population in this study are food and beverage companies listed on the Indonesia Stock Exchange. The sampling technique used was purposive. The sample of companies amounted to 12 companies. Data analysis techniques in this study used a logistic regression test. The results shows: (1) Auditor switching has no effect on audit quality, with the significance value of 0.177> 0.05 (2) Audit fee has no effect on audit quality with a significance value of 0.046 <0.05 (3) audit tenure has no effect on audit quality with a significance value of 0.229> 0.045 (4) Firm size has no effect on audit quality with a significance value of F of 0.031 <0.05